An updated methodology to estimate critical velocity in front crawl swimming: A scoping review - Petrigna, L.; Karsten, B.; Delextrat, A.; Pajaujiene, S.; Main, D.; Paoli, A.; Aplma, A.; Bianco, A. (Science & Sports, 2022)
Objectives Critical velocity and its related total distance covered above critical velocity can be used to evaluate and monitor the training and competition performance in athletes. While it is well researched in sports such as cycling and running, the literature on critical velocity in swimming is less available. Therefore, the objectives of this review are: (i) to methodologically evaluate the protocols used to obtain critical velocity; and (ii) eventually, to provide a standard operating procedure to evaluate critical velocity in front crawl swimming. Methods The review followed "Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews" guidelines. PubMed, Web of Science and Scopus were used to find original studies written in English. No exclusion criteria were adopted for the country of origin. The results were analysed through a narrative synthesis. News A total of 41 studies were included. Sixteen different protocols were adopted with different physiological thresholds as comparators with critical velocity. Conclusion Critical velocity evaluation presents different testing protocols, making this performance marker potentially inaccurate. As a consequence, we propose a standard operating procedure.